2019
DOI: 10.3389/fphar.2019.01207
|View full text |Cite
|
Sign up to set email alerts
|

The Signaling Pathways, and Therapeutic Targets of Antiviral Agents: Focusing on the Antiviral Approaches and Clinical Perspectives of Anthocyanins in the Management of Viral Diseases

Abstract: As the leading cause of death worldwide, viruses significantly affect global health. Despite the rapid progress in human healthcare, there are few viricidal and antiviral therapies that are efficient enough. The rapid emergence of resistance, and high costs, as well as the related side effects of synthetic antiviral drugs, raise the need to identify novel, effective, and safe alternatives against viral diseases. Nature has been of the most exceptional help and source of inspiration for developing novel multi-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 254 publications
(271 reference statements)
1
92
0
1
Order By: Relevance
“…Phytochemicals have similarly been shown to be of considerable importance in nutritional strategies for addressing the severity of viral respiratory diseases [62,168,169]. Apart from the ability of certain polyphenols to influence microbiota composition, they also impart antioxidant, anti-inflammatory, and anti-viral effects [170][171][172]. The antiviral effects of polyphenols have been demonstrated to be mediated either by direct inhibitory effects on virus replication or through the induction of immunomodulatory/antioxidant responses [170,171].…”
Section: Polyphenolic Plant Bioactivesmentioning
confidence: 99%
“…Phytochemicals have similarly been shown to be of considerable importance in nutritional strategies for addressing the severity of viral respiratory diseases [62,168,169]. Apart from the ability of certain polyphenols to influence microbiota composition, they also impart antioxidant, anti-inflammatory, and anti-viral effects [170][171][172]. The antiviral effects of polyphenols have been demonstrated to be mediated either by direct inhibitory effects on virus replication or through the induction of immunomodulatory/antioxidant responses [170,171].…”
Section: Polyphenolic Plant Bioactivesmentioning
confidence: 99%
“…It was suggested that these compounds might act against viral infection through the inhibition of virus adsorption [80]. The polysaccharides fucoidan, based on the sulfated L-fucose, possesses various biological activities, among them activities against many RNA and DNA viruses such as HIV, HSV1-2, dengue virus, and cytomegalovirus [81].…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…Anthocyanins are not only effective in the improvement of vascular health but also have antiviral properties. Inhibitory effects of anthocyanins [43] on different pathways involved in the virus life cycle have also been recently reviewed.…”
Section: Polyphenolsmentioning
confidence: 99%